Asymmetric Reductive Amination of Ketones Catalyzed by Imine Reductases. Issue 12 (19th May 2016) - Wetzl, Dennis; Gand, Martin; Ross, Alfred; Müller, Hubertus; Matzel, Philipp; Hanlon, Steven P.; Müller, Michael; Wirz, Beat; Höhne, Matthias; Iding, Hans
Abstract: Biocatalysis employing imine reductases is a promising approach for the one‐step generation of chiral amines from ketones. The enzymes reported for this process suffer from low activity and moderate stereoselectivity. We identified a set of enzymes that facilitate this reaction with high to quantitative conversions from a library of 28 imine reductases. This enabled the conversion of ketones with ammonia, methylamine, or butylamine into the corresponding amines. Most importantly, we performed preparative (>100 mg) scale syntheses of amines such as (1 S, 3 R )‐ N, 3‐dimethylcyclohexylamine and ( R )‐ N ‐methyl‐2‐aminohexane with excellent stereochemical purities (98 %  de, 96 %  ee ) in good yields. Abstract : Matching pairs : Imine reductases can form chiral amines by direct reductive amination from ketones. We investigate this reaction by screening a library of 28 imine reductases to identify suitable enzymes. The identified imine reductases are applied in the preparation of chiral amines at ketone concentrations up to 1 % w/v with excellent conversions (>95 %) and stereoselectivities (>94 %  ee or de ).